The Influence of Japanese Popular Culture on Children’s Toys Trends in Indonesia 1980-2010 (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is entitled The Influence of Japanese Pop Culture on Children’s Toys Trends in Indonesia, 1980-2010. The study employs the historical method, which consists of four stages: heuristics, source criticism, interpretation, and historiography.John Fiske’s (2011) theory of popular culture and Joseph Nye’s concept of soft power is used to analyze how Japanese popular culture, particularly through entertainment media and toy products, was disseminated persuasively and received by Indonesian children. Since the early 1990s, mass media such as television and children’s magazines have played an important role in introducing Japanese anime and characters, which subsequently encouraged the emergence of toy trends based on Japanese popular culture. The object of this research focuses on children’s toys influenced by Japanese popular culture that circulated in Indonesia between 1980 and 2010, including Tamiya, Beyblade, Tamagotchi, Crush Gear, B-Daman, and yo-yo. These toys not only developed as commercial products, but also contributed to the formation of children’s play patterns, communities, and social identities. However, during the period from 2008 to 2010, these toy trends began to decline due to the advancement of digital technology, changes in children’s consumption patterns, broadcast censorship policies implemented by Indonesian Broadcasting Commission (KPI), and increasing competition from popular culture of other countries such as Korea, the United States, and China. This condition reflects a shift in children’s play culture from physical toys to more modern forms of digital entertainment.